On the role of a social identity analysis in articulating structure and collective action: the 2011 riots in Tottenham and Hackney - Stott, Clifford John T. (The British journal of criminology, 2017)
Theoretical perspectives that give primacy to ideological or structural determinism have dominated criminological analysis of the 2011 English ‘riots’. This paper provides an alternative social psychological perspective through detailed empirical analysis of two of these riots. We utilize novel forms of data to build triangulated accounts of the nature of the events and explore the perspectives of participants. We assert these riots cannot be adequately understood merely in terms pre-existing social understandings and political realities and that identity-based interactional crowd dynamics were critically important. The paper demonstrates the value of the social identity approach in providing criminological theory with a richer and deeper perspective on these complex social phenomena.